Massachusetts Signing Bonus Program for New Teachers - Fowler, R. Clarke (Education Policy Analysis Archives, 2003)
This article examines the Massachusetts Signing Bonus Program for New Teachers, a nationally prominent program that has recruited and prepared 20,000 bonus recipients to teach after seven weeks' training at the Massachusetts Institute for New Teachers (MINT). Although state officials have trumpeted this initiative as a national model that other states are copying, they announced in November 2002 that they were radically changing it. The changes included halting the state's national recruitment efforts and replacing the seven-week, fast-track training program designed by the New Teacher Project with year-long programs to be designed by three of the state's education schools. Even though the state spent more than 50,000 recruiting individuals from states outside the Northeast over the first four program years, it garnered just seven bonus recipients from the non-Northeast states its recruiters visited, only four of whom were still teaching in Fall 2002. The state did, however, generate a substantial number of applicants in each program year (ranging from 783 to nearly 950), most of whom came from Massachusetts or nearby states. Contrary to state officials' claims, though, it appears that many of these individuals had substantial prior educational experience. Although officials stated that all bonus teachers would go to 13 designated high-need urban districts, the state has never met this commitment, sending fewer bonus teachers to these districts in each of the first three years of the program. The state has lost a high percentage of its bonus teachers to attrition particularly in state-designated, high-need districts. These attrition rates are substantially higher than comparable national rates. Although the state has portrayed the Bonus and MINT programs, combined, as highly successful, officials exaggerated many of the purported positive outcomes. On the positive side, independent survey data (Churchill et al., 2002) indicated that principals rated MINT graduates' performance favorably, when compared to traditionally-trained teachers. It is not clear, though, whether such ratings varied either by a) the extent of the teacher's prior educational experience or b) the nature of the teacher's placement (urban vs. suburban). The Bonus Program has produced relatively few urban teachers, relatively few minority teachers, and low rates of teacher retention, even though this effort was modeled after Teach for America and critical parts of it were designed and often managed by the New Teacher Project'two organizations that the Bush administration has praised for their ability to design and run programs of this type. Policy makers are urged to resist calls to embrace rapid certification, an approach that has produced, in Massachusetts, low numbers of urban teachers and high numbers of exiting teachers, all at a cost of more than four million dollars.